Parménides: una revelación de los infiernos. Silencio… (2009)
The purpose of this article is to describe Being in Parmenides's poem as the effect of a descend into the region of the underworld, where the Kouros embarks on a crossing. Epic of Being. "That which is": a truth that is produced in the underworld. Syrinx, syrinx, syrinx, syrinx...